A Variation on Strongly Ideal Lacunary Ward Continuity - Sengul, Hacer; Cakalli, Huseyin; Et, Mikail (Soc Paranaense Matematica, 2020)
The main purpose of this paper is to introduce the concept of strongly ideal lacunary quasi-Cauchyness of order (alpha, beta) of sequences of real numbers. Strongly ideal lacunary ward continuity of order (alpha, beta) is also investigated. Interesting results are obtained.
Keywords: Sequences; Series; Summability; Compactness; Continuity